Postoperative pain relief following inguinal hernia repair in children by wound infiltration with levobupivacaine. - Bari, MS; Haque, N; Talukder, SA; Chowdhury, LH; Zahid, MK; Hassanuzzaman, SM; Alam, MM; Huq, MA; Hasina, K; Khan, N; et al. (Mymensingh Medical Journal, 2012)
Mymensingh Med J. 2011 Oct;20(4):586-90 The abstract of this article is available on the PubMed website